2011
DOI: 10.1002/jcc.21877
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of self‐consistent‐field convergence by combining conventional diagonalization and a diagonalization‐free procedure

Abstract: A new scheme that combines conventional matrix diagonalization with the recently proposed diagonalization-free algorithm has been developed to obtain the density matrix for the next self-consistent-field iteration from the Fock matrix of the current iteration. In this manner, the advantages of the two methods are combined. The more rapid convergence of the diagonalization-free algorithm for density matrices rather close to self consistence and the more robust convergence of the conventional matrix diagonalizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Baldes et al found that the stability of the original algorithm strongly depended on the starting reference MOs. If the reference MOs were too distant from the solution of the SCF equation, very slow or no convergence of the SCF iterations and microiterations was observed.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Baldes et al found that the stability of the original algorithm strongly depended on the starting reference MOs. If the reference MOs were too distant from the solution of the SCF equation, very slow or no convergence of the SCF iterations and microiterations was observed.…”
Section: Methodsmentioning
confidence: 99%
“…If the reference MOs were too distant from the solution of the SCF equation, very slow or no convergence of the SCF iterations and microiterations was observed. To solve this problem, a hybrid scheme was suggested and implemented using the following idea: monitor the largest element max (t) and apply the diagonalization‐free step only if the pertinent amplitude does not exceed a threshold value set to 0.1. Otherwise, perform one diagonalization and obtain new and supposedly better reference MOs.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations